The Relationship Between Hardiness, Personality Traits and Coping Styles with Occupational Satisfaction Among the Nurses of Governmental Hospitals in Tabriz - Zeynab Khanjani; Malikeh Raef; Mostafa Asgari (Hamadan University of Medical Sciences, 2018)
Introduction: The purpose of this study is to determine the relationship between hardiness, personality traits and coping styles with job satisfaction among nurses in state hospitals in Tabriz. Methods:This is a descriptive- correlational study and the statistical population is consisted of nurses working in Tabriz hospitals. The sample consisted of 320 people selected by multi-stage random sampling who responded to four questionnaires: job satisfaction, neo personality, hardiness and coping with the stressful situation. The questionnaires were analyzed by SPSS 16. Results: The results of this study showed that job satisfaction and neuroticism have a negative and meaningful relationship. On the other side, job satisfaction has a positive and meaningful relationship with flexibility, conscientiousness and extraversion. There is no meaningful relationship between pleasure and job satisfaction. Also a positive relationship exists between the problem-oriented coping style and pleasure. There is a negative relation between the emotional-avoidance, coping styles and avoidance with the job satisfaction. Hardiness components had a positive and meaningful relationship with job satisfaction. Also, multivariate regression showed that among predictor variables only the psychoanalytic, flexibility and conscientious variables were able to predict the job satisfaction of nurses. Among the coping styles, the problem-based and avoidance style pre-emptive variables on job satisfaction were effective. All three hardiness components were able to predict the job satisfaction of nurses. Conclusion: The results showed that two dimensions of flexibility and neuroticism had a predictive role in the job satisfaction of nurses. According to the results, in addition to evaluating the public talents and abilities in employee selection, these two dimensions of personality may be more noteworthy.